2012
DOI: 10.1186/1756-0500-5-603
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a 23S ribosomal RNA mutation in Helicobacter pylori strains on the in vitro synergistic effect of clarithromycin and amoxicillin

Abstract: BackgroundClarithromycin (CLR) is the most commonly recommended antibiotic in Helicobacter pylori eradication regimens, but the prevalence of CLR-resistant H. pylori is increasing. CLR resistance is associated with mutations in the 23S rRNA gene. However, H. pylori eradication can still be achieved with triple therapy, and an additive effect may occur with multiple antibiotics.MethodsTwenty-six CLR-resistant strains were examined. The MIC of clarithromycin was determined by agar-dilution-testing on Columbia ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 7 publications
0
7
1
Order By: Relevance
“…We found a higher prevalence of A2143G compared to A2142G mutation in our samples which is in agreement with the majority of Brazilian studies including the States of Minas Gerais, São Paulo and Recife [ 20 , 34 , 36 ]. A2143G but not A2142G point mutation shows a synergistic effect of clarithromycin and amoxicillin, which have been used together in the first-line H. pylori regimen [ 49 ], reinforcing the necessity to investigate this clarithromycin 23S rDNA point mutation before treatment. One sample harbored both A2142G and A2143G mutations at domain V of the H. pylori 23S rDNA that was also found in three H.pylori isolates obtained from patients of the Brazilian State of Minas Gerais [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…We found a higher prevalence of A2143G compared to A2142G mutation in our samples which is in agreement with the majority of Brazilian studies including the States of Minas Gerais, São Paulo and Recife [ 20 , 34 , 36 ]. A2143G but not A2142G point mutation shows a synergistic effect of clarithromycin and amoxicillin, which have been used together in the first-line H. pylori regimen [ 49 ], reinforcing the necessity to investigate this clarithromycin 23S rDNA point mutation before treatment. One sample harbored both A2142G and A2143G mutations at domain V of the H. pylori 23S rDNA that was also found in three H.pylori isolates obtained from patients of the Brazilian State of Minas Gerais [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…demonstrated that the combination of clarithromycin and metronidazole has synergistic activity against 50% of tested H. pylori strains . In one study, synergism between clarithromycin and amoxicillin was only observed for clarithromycin‐susceptible isolates while in another, synergism was noted in the presence of a mutation at position A2143G, but not in the presence of one at position at A2142G . Indirect evidence for this synergy between amoxicillin and clarithromycin was suggested in a small study from Japan where triple regimens containing amoxicillin prevented the selection of secondary clarithromycin resistance compared to non‐amoxicillin‐containing regimens .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the A2143G point of mutation has been shown to significantly affect the eradication rate of H. pylori. Consequently, investigating the distribution of each mutated genotype for resistance to clarithromycin is relevant for managing H. pylori in clinical practice (Sakinc et al, 2012). Thus, various studies have been performed in order to identify the relationship of the mutated genotypes with the bacterial genetic factors involved in virulence and clarithromycin sensitivity (Vannarath et al, 2014;Agudo et al, 2010;Garcia et al, 2010).…”
Section: Introductionmentioning
confidence: 99%